Aboriginal Health Workers experience multilevel barriers to quitting smoking: a qualitative study - Dawson Anna P; Cargo Margaret; Stewart Harold; Chong Alwin; Daniel Mark (BMC, 2012)
Abstract Introduction Long-term measures to reduce tobacco consumption in Australia have had differential effects in the population. The prevalence of smoking in Aboriginal peoples is currently more than double that of the non-Aboriginal population. Aboriginal Health Workers are responsible for providing primary health care to Aboriginal clients including smoking cessation programs. However, Aboriginal Health Workers are frequently smokers themselves, and their smoking undermines the smoking cessation services they deliver to Aboriginal clients. An understanding of the barriers to quitting smoking experienced by Aboriginal Health Workers is needed to design culturally relevant smoking cessation programs. Once smoking is reduced in Aboriginal Health Workers, they may then be able to support Aboriginal clients to quit smoking. Methods We undertook a fundamental qualitative description study underpinned by social ecological theory. The research was participatory, and academic researchers worked in partnership with personnel from the local Aboriginal health council. The barriers Aboriginal Health Workers experience in relation to quitting smoking were explored in 34 semi-structured interviews (with 23 Aboriginal Health Workers and 11 other health staff) and 3 focus groups (n = 17 participants) with key informants. Content analysis was performed on transcribed text and interview notes. Results Aboriginal Health Workers spoke of burdensome stress and grief which made them unable to prioritise quitting smoking. They lacked knowledge about quitting and access to culturally relevant quitting resources. Interpersonal obstacles included a social pressure to smoke, social exclusion when quitting, and few role models. In many workplaces, smoking was part of organisational culture and there were challenges to implementation of Smokefree policy. Respondents identified inadequate funding of tobacco programs and a lack of Smokefree public spaces as policy level barriers. The normalisation of smoking in Aboriginal society was an overarching challenge to quitting. Conclusions Aboriginal Health Workers experience multilevel barriers to quitting smoking that include personal, social, cultural and environmental factors. Multidimensional smoking cessation programs are needed that reduce the stress and burden for Aboriginal Health Workers; provide access to culturally relevant quitting resources; and address the prevailing normalisation of smoking in the family, workplace and community.